Protective Effects of Resveratrol against Chronic Immobilization Stress on Testis. (6th November 2013) - Bitgul, Gulsah; Tekmen, Isil; Keles, Didem; Oktay, Gulgun
Abstract : Objective . The aim of this study was to investigate protective effects of resveratrol, a strong antioxidant, against possible negative effects of chronic immobilization stress on testes of male rats histochemically, immunohistochemically, ultrastructurally, and biochemically. Material and Methods . Male Wistar rats were divided into 4 groups (n = 7 ). Group I, control group (C), was not exposed to stress. Group II, stress group (S), was exposed to chronic immobilization stress. In Group III, low dose resveratrol + stress group (LRS), rats were given 10 mg/kg/day resveratrol just before the stress application. In Group IV, high dose resveratrol + stress group (HRS), rats were given 20 mg/kg/day resveratrol just before the stress application. For chronic immobilization stress application animals were put in the plastic tubes (6 cm in diameter, 15 cm in length) during 32 days for 6 hours. All animals were sacrificed 18 hours after the last stress application. Results . Histochemical and ultrastructural investigations showed that in stress group there was germ cell deprivation in seminiferous tubules and increase of connective tissue on interstitial area. No significant changes were seen in low and high dose resveratrol groups. After immunohistochemical investigations, TUNEL (+) and Active Caspase-3 (+) cells were increased in seminiferous tubules of stress group compared with those control group, but they were decreased in low and high dose resveratrol groups. According to biochemically results, MDA, GSH, and testosterone levels in stress group showed no significant difference when compared with those of the other groups. Conclusion . The chronic immobilization stress increases oxidative stress and apoptosis and causes histological tissue damages; resveratrol can minimize the histological damage in testes significantly.